The Effectiveness of the Waste Bank Program through a Community Participation Approach: A Review of the Literature - Amri, Khairul; Adifa, Fitri (Journal of Law, Politic and Humanities, 2022)
The escalating waste problem in various regions of Indonesia highlights the need for a waste management approach that not only relies on government policies but also emphasizes active community involvement. The waste bank program has emerged as a strategic alternative and has been widely implemented. However, despite its widespread application, the success rate of waste banks remains varied, primarily due to fluctuating levels of public participation. This study aims to analyze the effectiveness of waste bank programs through a community participation approach, identify key challenges, and formulate strategies to enhance program effectiveness based on a literature review. The method employed is a qualitative literature study of ten relevant academic articles. The findings show that the effectiveness of waste banks is influenced by active community participation, managerial capacity, policy support, and multi-stakeholder collaboration. These findings indicate that the success of waste banks depends not only on economic incentives, but also on environmental literacy and community leadership in fostering public awareness to care for the environment.